Analysis Push-Pull Mooring Factors on Switching Intention Banking Customers - Alfath Prasetya Agung Nugraha; Afriapollo Syafaruddin (Sultan Publisher, 2023)
This study aims to determine the intention of conventional banking customers to switch to digital banking. The purpose of this study was to analyze the relationship between dependent switching intention, with independent variables of service quality, information seeking behavior, alternative attractiveness, and individualism level as moderation variables. This research uses the big theory approach of Push-Pull Mooring. Then this research methodology uses a quantitative approach through survey methods. Data processing using the Partial Least Square (PLS) method. The results of this study show that push variables (service quality, and information seeking behavior) have a significant influence on the switching intention, and pull variables (alternative attractiveness) have a significant influence on the switching intention, then mooring variables (individualism level) can moderate service quality variables, and alternative attractiveness, while information search behavior variables cannot be moderated, then moderation variables have an effect significant to the switching intention.